Analysis of torsadogenic and pharmacokinetic profile of E-4031 in dogs bridging the gap of information between in vitro proarrhythmia assay and clinical observation in human subjects - Ai Goto; Hiroko Izumi-Nakaseko; Mihoko Hagiwara-Nagasawa; Koki Chiba; Kentaro Ando; Atsuhiko T. Naito; Atsushi Sugiyama (Elsevier, 2018)
We analyzed torsadogenic and pharmacokinetic profile of E-4031 using chronic atrioventricular block dogs. E-4031 in intravenous doses of 0.03, 0.1 and 0.3 mg/kg over 10 min prolonged QT/QTc, and increased short-term variability of QT in a dose-related manner (n = 4), resulting in onset of torsade de pointes in 1 animal after the middle dose and 4 animals after the high dose, while it attained peak plasma concentrations of 16.5, 60.5 and 182.5 ng/mL at 10 min after their start of administration, respectively (n = 2). These results bridge the gap of information between in vitro proarrhythmia assay and clinical observation in human subjects. Keywords: E-4031, Torsade de pointes, CiPA